MEDICO-LEGAL STUDY OF FATAL INCISED WOUNDS IN BAGHDAD (Iraqi Journal of Medical Sciences, 2016)
Background:Sharp force injuries and fatalities have been reported to be the most common crimes of violence in several countries, predominantly in those where access to firearms is restricted. Death due to sharp force violence is the most common cause of homicidal deaths in Sweden and in many other countries in Europe, Africa and Asia. However incised wounds are less common in homicide.Objective Method:A medico-legal descriptive study conducted on 18 autopsies during 6 months period. Cases were studied according to their age, sex, scene of incident, number of injuries, presence of other types, suggestive manner of injury and anatomical regions affected. Blood sample was taken for alcohol detection then complete classical autopsy was done.Results:Incised wound cases were about a third of total sharp wound cases. Males were 5 times more frequently involved than females with an age range 36.4±29.1. Indoor and outdoor scene of incidents was almost equal. Most of them were multiple with mixed types of sharp wounds. Suggestive homicidal manner of death was seen. The neck was the most common anatomical region affected. There was no role of alcohol in causation of such injuries.Conclusion:Incised wounds are infrequently encountered in medico-legal autopsy practice. Males seem to be more prone to such injuries with multiple and mixed types in the majority of cases. Homicidal manner was suggested in all cases and neck was the preferable site for the perpetrator.Keywords:Incised wound, sharp wound, autopsy, Homicide.
Keywords: Incised wound; sharp wound; autopsy; Homicide